Factors associated with the incidence of low birth weight (LBW) in pregnant women with HIV/AIDS - Dartiwen, Dartiwen; Maslikhah, Ikha (International Journal of Health Science and Technology, 2024)
The high number of HIV/AIDS cases in pregnant women has an impact on maternal and infant mortality. Based on data on new HIV/AIDS cases recorded in the HIV/AIDS Information System at Bhayangkara Indramayu Hospital, the number of pregnant women with HIV/AIDS in 2023 is 62 people and LBW is 31 babies. The purpose of this study is to find out the factors related to the incidence of LBW in pregnant women with HIV/AIDS at Bhayangkara Hospital. The research method uses quantitative research with a cross-sectional approach. The population is all maternity mothers with HIV/AIDS for the January-December 2023 period at Bhayangkara Hospital, with as many as 62 people. Sampling uses total sampling. Data collection uses secondary data by looking at HIV/AIDS reactive maternal medical records. Data analysis uses univariate and bivariate analysis with the Chi-Square test. The results showed that the factors related to the incidence of LBW in pregnant women with HIV/AIDS were the number of CD4 (p-value = 0.038), clinical stage (p-value = 0.029), haemoglobin level (p-value = 0.042), and comorbidities during pregnancy (p-value = 0.042). Pregnant women are advised to do voluntary HIV testing, make regular ANC visits to health facilities, conduct Voluntary Counseling and Testing, and consume antiretroviral drugs regularly and regularly to suppress the multiplication of the HIV in the body.